2020
DOI: 10.1039/c9cp06954b
|View full text |Cite
|
Sign up to set email alerts
|

The misfolding mechanism of the key fragment R3 of tau protein: a combined molecular dynamics simulation and Markov state model study

Abstract: All-atom molecular dynamics (MD) simulation combined with Markov state model (MSM) were used to uncover the structural characteristics and misfolding mechanism of the key R3 fragment of tau protein at the atomic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…After careful evaluation of convergence, the probability distributions of the α-helix and β-sheet content were found to be dissimilar (Figure A) for four tautomeric isomers, indicating that different neutral histidine tautomeric conditions (ε or δ) at positions 268 and 299 can affect the organizational and aggregation features of the tau monomer. The conformational change of tau from the native disorder state to the β-sheet rich structure is the significant feature of the production of tau fibrils . Thus, exploring the formation mechanism of the tau β-sheet rich structure is important to understand the pathogenic mechanism of different tauopathies.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After careful evaluation of convergence, the probability distributions of the α-helix and β-sheet content were found to be dissimilar (Figure A) for four tautomeric isomers, indicating that different neutral histidine tautomeric conditions (ε or δ) at positions 268 and 299 can affect the organizational and aggregation features of the tau monomer. The conformational change of tau from the native disorder state to the β-sheet rich structure is the significant feature of the production of tau fibrils . Thus, exploring the formation mechanism of the tau β-sheet rich structure is important to understand the pathogenic mechanism of different tauopathies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, within εε, εδ, and δε isomers, α-helices can be formed mostly at K14–V21 (content: 40–84%), K14–leucine (L18) (content: 45–85%), and K14–Q22 (content: 29–56%; Figure D). Overall, owing to high β-sheet secondary structure content, isomer δδ may play a supreme role in tau fibrilization and/or aggregation because the β-sheet content is the primary component that produces tau fibrils. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research suggested that the conformation of tau monomer may play an important role in the NFTs formation process, especially in the initial stage. 10 More recently, Mirbaha et al classified the conformations of tau monomer into two general categories: inert (M i ) monomer and seed-competent (M s ) monomer. 11 Differing from M i , M s indicates a tendency of self-aggregation and seeding activity.…”
Section: ■ Introductionmentioning
confidence: 99%